2021
DOI: 10.1016/j.jhepr.2020.100194
|View full text |Cite
|
Sign up to set email alerts
|

The importance of adequate oxygenation during hypothermic machine perfusion

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 14 publications
(23 reference statements)
1
11
0
Order By: Relevance
“…The median recipient age was 59 (53-65) years and the majority was male (78%). Prior to liver transplantation, the median BAR score was 5 (3)(4)(5)(6)(7)(8). The most common indications for liver transplantation were alcoholic cirrhosis (22%), hepatocellular carcinoma (17%), and nonalcoholic steatohepatitis (16%).…”
Section: Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…The median recipient age was 59 (53-65) years and the majority was male (78%). Prior to liver transplantation, the median BAR score was 5 (3)(4)(5)(6)(7)(8). The most common indications for liver transplantation were alcoholic cirrhosis (22%), hepatocellular carcinoma (17%), and nonalcoholic steatohepatitis (16%).…”
Section: Study Populationmentioning
confidence: 99%
“…Hypothermic oxygenation of mitochondria induces metabolic programming within 1 h, thereby decreasing mitochondrial succinate accumulation and uploading adenosine triphosphate levels 2 . Reperfusion of livers treated by end‐ischemic HOPE is, therefore, associated with less oxidative injury and mitochondrial damage with subsequently less downstream inflammation 2‐4 …”
Section: Introductionmentioning
confidence: 99%
“…The initial transplantation-related research was performed by Thuillier et al They demonstrated that Hemarina M101 has a beneficial effect during SCS before kidney transplantation by decreasing chronic fibrosis and organ dysfunction [ 82 ]. Alix et al compared SCS solution with Hemarina M101 versus SCS solution alone during porcine liver graft preservation, showing higher ATP levels in the SCS with Hemarina M101 group after 80 min [ 42 , 83 ]. M101 was also used in preclinical trials as an additive to the perfusion solution during HMP in a marginal kidney porcine model.…”
Section: Overview Of Oxygen Carriersmentioning
confidence: 99%
“…The [42,83]. M101 was also used in preclinical trials as an additive to the perfusion solution during HMP in a marginal kidney porcine model.…”
Section: Natural Extracellular Oxygen Carrier Hemarina M101mentioning
confidence: 99%
“…End-ischemic preservation by HOPE, on the other hand, is able to restore ATP content by multifold. 21 The limited effect of an oxygenated flush on ATP could partly be explained by the short duration of oxygenation (only during several minutes of in situ donor flush compared with 1-2 h HOPE). Theoretically, the flush out time can be prolonged to enhance the effect of F I G U R E 4 Cholangiocellular function during 4 h of normothermic reperfusion.…”
Section: Discussionmentioning
confidence: 99%